The coefficient of reflect ion of ultrasonic waves from an adhesive bond interface - PILARSKI, Aleksander (Archives of Acoustics, 1983)
This paper reports on an attempt to explain the existence of a relation between the reflection coefficient and mechanical strength of an adhesive bond, based on a model of a bond with finite rigidity. On the basis of formulae derived, a correlation relation was determined from experimental results between the modulus of the pressure reflection coefficient of a plane ultrasonic wave incident normal to the interface of an adhesive bond of Incite with epoxy resin, and the tensile strength of the bond.